2019
DOI: 10.1039/c9ra02013f
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic and excellent microwave absorbing properties of CoNi microspheres and heterogeneous Co/Ni nanocrystallines

Abstract: CoNi microspheres with different diameters and heterogeneous Co/Ni nanocrystallines were synthesized via changing hydrothermal reaction parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The preferred RL value is −20 dB, with a microwave absorption efficiency of about 99% . In almost all cases, ,, the absorption properties have been investigated by controlling the sheet thickness of the composite, and the investigation related to Co–Ni alloy nanoparticles is hardly reported. In this study, as in the above reports, the microwave absorption properties are evaluated by varying the thickness of Co–Ni core–shell and Co–Ni alloy–polyethylene composite sheets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preferred RL value is −20 dB, with a microwave absorption efficiency of about 99% . In almost all cases, ,, the absorption properties have been investigated by controlling the sheet thickness of the composite, and the investigation related to Co–Ni alloy nanoparticles is hardly reported. In this study, as in the above reports, the microwave absorption properties are evaluated by varying the thickness of Co–Ni core–shell and Co–Ni alloy–polyethylene composite sheets.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the difficulty in large-scale synthesis of either FeCo or FeNi, Co–Ni nanocrystals that also possess high saturation magnetization and high magnetic permeability have attracted considerable attention as microwave absorbers. ,,, The microwave absorption properties of Co–Ni alloys attributed to ferromagnetic, dielectric, and eddy current losses are influenced by the particles’ morphology, size, and structure. Composites of Co 50 Ni 50 , or Co 20 Ni 80 , particles with varying sheet thicknesses have been studied in frequencies between 2 and 18 GHz, , and a maximum RL value of −34 dB at 3 GHz has been reported .…”
Section: Introductionmentioning
confidence: 99%
“… Sample Filling ratio (wt %) Minimum RL value RL ≤ − 10 dB References d m (mm) RL min (dB) d m (mm) f e (GHz) CoNi microspheres 60 2.5 − 41 1.5 4.16 Ref. 41 CoNi microflowers 20 2 − 28.5 2 6.5 Ref. 42 Co 67 Ni 33 /Ni 0.6 Zn 0.4 Fe 2 O 4 60 2.1 − 43.8 2.1 5 Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Microwave absorption corresponding to a reflection loss of −10 dB, which is considered suitable for a microwave absorber, was observed in RAS 5 and RAS 6, with a thickness of 4 mm. In a recent study [36], a 3-GHz bandwidth and an RL of −33 dB at 17.6 GHz were achieved; however, a high weight percentage (60%) of magnetic filler was required. In this work, RAS 5 exhibited a maximum RL of −33 dB at a frequency of 9.6 GHz while only requiring 10 and 25 wt-% of NZF in the first and second layers, respectively.…”
Section: Reflection Loss Of Double-layered Radarabsorbing Structuresmentioning
confidence: 99%
“…The combination of polyaniline (PANI) coated MWCNTs with manganese zinc ferrite exhibited a maximum RL of −32.5 dB at 10.8 GHz [33]. The drawback of the magnetic materials that have been used as radar-absorbing materials in the literature is that they are effective only when used in high weight percentages [8, 20, 26, 29, 34-37]; this leads to an increase in the overall weight of the structure. Additionally, no significant research has been found with regard to their utilisation in RASs, especially those of NZF; this is true even though their chemical synthesis methods are relatively simple when compared to the RASs of dielectric materials [9, 21-25, 27].…”
Section: Introductionmentioning
confidence: 99%